Efektivitas Program Posyandu Lansia dalam Meningkatkan Kesejahteraan Lansia di Desa Pak Laheng Kecamatan Toho - Lusi, Brigida; Musa, Dahniar Th; Apriyani, Eka; Reza, Lorensia; Vera, Janiva; Syakila, Risty (Jurnal Intervensi Sosial dan Pembangunan, 2024)
The elderly posyandu program in Pak Laheng Village still lacks participation from the elderly to attend posyandu every month regularly. The purpose of this study was to describe the effectiveness of the elderly posyandu program in improving the welfare of the elderly in Pak Laheng Village, Toho District. This research uses Dunn's policy evaluation theory, namely Effectiveness, with five indicators, namely program understanding, on target, timeliness, goal achievement, and real change. The research method used is descriptive qualitative. Data collection techniques were obtained by observation, interviews, and documentation. The data sources used in this research are primary and secondary data. In addition, the determination of informants was carried out using purposive sampling technique. The results of this study indicate that the implementation of the posyandu program for the elderly in Pak Laheng Village, Toho District can be said to be ineffective because based on the five indicators of effectiveness, it only meets two indicators, namely right on target and real change, while the other three indicators, namely program understanding, timeliness, and goal achievement are still lacking in success in achieving the effectiveness of the posyandu program for the elderly in Pak Laheng Village.Keywords: Elderly; Effectiveness, Posyandu Program; Welfare.